tRNA Metabolism and Lung Cancer: Beyond Translation - Bian, Meng; Huang, Shiqiong; Yu, Dongsheng; Zhou, Zheng (Frontiers in Molecular Biosciences, 2021)
Lung cancer is one of the malignant tumors with the fastest increase in morbidity and mortality, which poses the greatest threat to the health and life of the population. It is urgent to fully understand the pathogenesis of lung cancer and provide new ideas for its treatment. Interestingly, accumulating evidence has identified that transfer RNAs (tRNAs) and tRNA-associated biogenesis proteins not only participate in protein translation, but also play an important role in the occurrence and development of lung cancer. Therefore, this paper systematically summarizes the different aspects of tRNA metabolism in lung cancer, such as tRNA transcription and mutations, tRNA molecules and derivatives, tRNA modifications as well as tRNA aminoacylation, aiming at a better understanding of the pathogenesis of lung cancer and providing new therapeutic strategies for it.